Evaluation of the anticancer effects exerted by 5-fluorouracil and heme oxygenase-1 inhibitor hybrids in HTC116 colorectal cancer cells - Loredana Salerno; Antonietta Notaro; Valeria Consoli; Federica Affranchi; Valeria Pittalà; Valeria Sorrenti; Luca Vanella; Michela Giuliano; Sebastiano Intagliata (Journal of Enzyme Inhibition and Medicinal Chemistry, 2024)
Colon cancer remains a clinical challenge in industrialised countries. Its treatment with 5-Flurouracil (5-FU) develops many side effects and resistance. Thus, several strategies have been undertaken so far, including the use of drug cocktails and polypharmacology. Heme oxygenase-1 (HO-1) is an emerging molecular target in the treatment of various cancers. We recently demonstrated that a combination of HO-1 inhibitors with 5-FU and the corresponding hybrids SI1/17, SI1/20, and SI1/22, possessed anticancer activity against prostate and lung cancer cells. In this work, we evaluated these hybrids in a model of colon cancer and found that SI1/22 and the respective combo have greater potency than 5-FU. Particularly, compounds inhibit HO-1 activity in cell lysates, increase ROS and the expression of HO-1, SOD, and Nrf2. Moreover, we observed a decrease of pro-caspase and an increase in cleaved PARP-1 and p62, suggesting apoptotic and autophagic cell death and potential application of these drugs as anticancer agents.